Тайны серых кхоров: [фантастический] роман / Ален Лекс - Лекс Ален (Магия фэнтези, 2008)
Экземпляры: ф.11 (20170905) / Инвентарный номер: 57377 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Л 43 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445